(untitled) (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
Background: During Ramadan fasting there are changes in meal frequency, eating pattern, rhythm in life, the sleep cycle, and daily activity. Most people with uncomplicated type 2 DM (T2DM) fast during Ramadan in Bangladesh. Objective: To assess the knowledge, attitude, and practices of people of Bangladesh with T2DM about Ramadan fasting. Methods: The survey enrolled 3835 adult people with T2DM (age 49.4±11.8 years; mean±SD; 57.4% female) through 17 endocrine outpatient centers in Bangladesh. Patient enrolment started one month before Ramadan in 2021. The survey questionnaire comprised 25 questions that addressed the characteristics of study subjects, their knowledge and attitude towards fasting, their lifestyle, and usual practices to control blood glucose during Ramadan. Result: About 83.3% of participants intend to fast. Most were aware of the necessity of pre & post-Ramadan health checkups (48% and 77% respectively). The participants were aware of risks during fasting like hypoglycemia (58.6%), dehydration (64.6%) & uncontrolled DM (74.0%). Near seventy percent answered that they could control diabetes by themselves, and similar proportion did follow the doctor’s advice of medication adjustment. The necessity of glucose monitoring was known by 47% while 49% knew what to do if hypoglycemia occurs. However, 36.9% believed finger pricking would break the fast; and 18% said they would not break the fast despite hypoglycemia. Conclusion: Most Bangladeshi adults with T2DM fast during Ramadan, and their knowledge, attitude, and practices are good, but still, some have myths, particularly about monitoring of blood glucose by finger pricking & breaking fast due to hypoglycemia during Ramadan fasting. J Assoc Clin Endocrinol Diabetol Bangladesh, July 2022; 1 (2): 50-54